Obstacles to scientific publishing in scientific journals classified within the (ISI) and (Scopus) databases from the point of view of faculty members in some universities in Arab countries - Al-Dabbagh, Maha Abdullah (Journal of Educational and Psychological Sciences, 2023)
This study sought to identify the most prominent obstacles to publishing in international refereed scientific journals classified within the (ISI) and (Scopus) databases from the faculty members' point of view, the extent of their interest in conducting research and publishing it in international refereed journals. It also shed light on the significance of publishing in refereed journals for faculty members and the most important opportunities that publishing in journals provides for faculty members and most of the bodies in which studies, research and books are published. The study used the descriptive-analytical approach. The researcher used a questionnaire to reveal the obstacles to scientific publishing in international refereed scientific journals. The questionnaire consisted of (20) phrases using a five-point scale (agree, strongly agree, neutral, disagree, Strongly Disagree). The study sample was limited to 200 faculty members in some Saudi and non-Saudi universities. The study found several obstacles to publication in international refereed journals, including the lengthy period spent in the research refereeing process, the high cost of publishing in international refereed scientific journals, the large teaching load, and the multiplicity of routine procedures associated with submitting and receiving research for publication in international refereed scientific journals classified, and the length of time taken in the process of receiving research published in international scientific journals. The study came out with several recommendations, the most important of which is the need to launch a unified website for Arab universities that includes fixed and transparent standards that serve as the primary reference for researchers in the Arab world concerning the rules of scientific authorship and publication.
Keywords: Scientific Publishing; ISI; Scopus